Aplicação de simulações computacionais no ensino de física - Santos, Admilson Nelson dos (2017)
Over time we have come across the strong influence of technologies on education as well as on the environment inside and outside the classroom. This shows that traditional classes, taught in the same way as they were decades ago, have been losing space for the competition of cell phones, applications, social networks, which are often more attractive to students than traditional classes. In this sense, this work aims to assist the teacher in the use of new technologies for the teaching of electrostatic physics. The purpose of the project was to create, elaborate and make available the scripts of an educational product that will help the teacher in the use of computational simulations in the teaching of electricity concepts in high school. It is hoped that the product can provide the teacher and the students with a new tool, computational simulation, that shows the physical phenomena to approach concepts in physics teaching. Thus, making learning more attractive and allowing the student to construct meaningful knowledge.